Performance Measurement System and Lecturers’ Performance: Testing The Mediation Role of Competency In Malaysian Research Universities - Janudin, Sharul Effendy; Maelah, Ruhanita; Amir, Amizawati Mohd; Abdullah, Nor Liza (International Business Education Journal, 2015)
Since performance of lecturers is the key contributor of academic excellence, universities need to empower their human capital to be competitive and subsequently achieve world-class status. Unfortunately, efforts to conduct research on measuring the performance of higher education institutions face a major setback compared to other industries due to its complex nature and difficulty in measuring its outputs. Furthermore, a review of literature indicates that research conducted in the education environment mainly focuses on organizational performance rather than work performance. This study fills the gap by providing a research framework focusing on the Theory of Work Performance. The interaction between performance measurement system and competency on the work performance of lecturers at the individual level was investigated through the analysis of data gathered from 368 academic staff from five Malaysian research universities. The findings indicate that 1) performance measurement system (PMS) is positively associated with lecturers’ performance; 2) competency is positively associated with lecturers’ performance; 3) competency partially mediates the relationship between performance measurement system and lecturers’ performance.